Antinociceptive action of oxytocin involves inhibition of potassium channel currents in lamina II neurons of the rat spinal cord - Darbon Pascal; Poisbeau Pierrick; Breton Jean (SAGE Publishing, 2009)
Abstract Background Growing evidence in the literature shows that oxytocin (OT) has a strong spinal anti-nociceptive action. Oxytocinergic axons originating from a subpopulation of paraventricular hypothalamic neurons establish synaptic contacts with lamina II interneurons but little is known about the functional role of OT with respect to neuronal firing and excitability. Results Using the patch-clamp technique, we have recorded lamina II interneurons in acute transverse lumbar spinal cord slices of rats (15 to 30 days old) and analyzed the OT effects on action potential firing ability. In the current clamp mode, we found that bath application of a selective OT-receptor agonist (TGOT) reduced firing in the majority of lamina II interneurons exhibiting a bursting firing profile, but never in those exhibiting a single spike discharge upon depolarization. Interestingly, OT-induced reduction in spike frequency and increase of firing threshold were often observed, leading to a conversion of the firing profile from repetitive and delayed profiles into phasic ones and sometimes further into single spike profile. The observed effects following OT-receptor activation were completely abolished when the OT-receptor agonist was co-applied with a selective OT-receptor antagonist. In current and voltage clamp modes, we show that these changes in firing are strongly controlled by voltage-gated potassium currents. More precisely, transient IA currents and delayed-rectifier currents were reduced in amplitude and transient IA current was predominantly inactivated after OT bath application. Conclusion This effect of OT on the firing profile of lamina II neurons is in good agreement with the antinociceptive and analgesic properties of OT described in vivo.